Decaffeinated resistance: Social constructions of wage theft in Melbourne’s hospitality industry - Ferris, Emma (Journal of criminology, 2023)
Wage theft, or the illegal non-payment of employee entitlements, is a pernicious and highly prevalent practice in industries across Australia, but particularly in hospitality. Despite recent media attention to cases involving some high-profile employers, little is known about how wage theft is experienced or understood by employees or the public. This research examines how wage theft is constructed and negotiated by employees and community members. Participants' constructions of wage theft reflected the consumerist, managerialist and individualist logics that have emerged in the wake of the intensive neoliberal restructuring of our economies and workplaces over the past three decades. It is argued that these views are also reflected in the current criminal enforcement regime that frames underpayment as a problem of rogue actors, rather than a social and structural issue. To disrupt the societal and disciplinary acceptance of wage theft, further criminological studies should aim to map out the direct and indirect harms arising from wage theft